A View on the Covid-19 Epidemic from the Perspective of Intersectoral Differences in Destandardisation and Employment Instability in Slovenia - Jožica Čehovin Zajc; Branko Bembič (Družboslovne Razprave, 2021)
In this paper, we analyse effects of the first wave of the COVID-19 epidemic on employment in Slovenia in the light of some theories on the destandardisation and segmentation of employment. We consider statistical databases, state measures and policies, along with union strategies before and during the epidemic. The epidemic has caused a sharp decline in employment and hit hardest those workers holding non-standard forms of employment (especially students and temporary workers). Given the decline in service turnover/production volume, particular service industries (e.g. retail, exports) have been more affected by export-oriented manufacturing that has invested less in employee skills and shifted the effects of the shock to labour and the state. We also note the trade unions have not deepened the splits in labour market divisions, while segmentation has been strengthened by both pre- and post-epidemic state policies.